PENGELOLAAN PROGRAM PENDIDIKAN KESETARAAN PAKET B DI SPNF SKB KABUPATEN KARAWANG - Firmansyah, Budi; Marlina, Rina; Suminar, Uum (Comm-Edu (Community Education Journal), 2025)
This study aims to describe and analyze the management of the Paket B Equivalency Education Program at SPNF Sanggar Kegiatan Belajar (SKB) in Karawang Regency. The research focuses on four main aspects: planning, implementation, evaluation, and the supporting and inhibiting factors of the program. A descriptive qualitative approach was employed, with data collected through in-depth interviews, direct observation, and documentation. The findings reveal that the program is managed systematically, beginning with community-based needs assessment, flexible curriculum planning, and adult-centered learning approaches, followed by continuous program evaluation. Supporting factors include local community involvement, institutional partnerships, and learners’ enthusiasm. Conversely, obstacles include limited facilities, mismatch between tutor backgrounds and adult education principles, and low parental involvement. The study recommends strengthening institutional management and enhancing community participation to improve the effectiveness of community-based non-formal education services.